Bone and mineral metabolism in patients with primary aldosteronism: A systematic review and meta-analysis - Wang, Anning; Wang, Yuhan; Liu, Hongzhou; Hu, Xiaodong; Li, Jiefei; Xu, Huaijin; Nie, Zhimei; Zhang, Lingjing; Lyu, Zhaohui (Frontiers in Endocrinology, 2022)
Purpose Patients with primary aldosteronism (PA) tend to exhibit a high prevalence of osteoporosis (OP) that may vary by whether PA is unilateral or bilateral, and responsive to PA treatment. To explore relationships between bone metabolism, PA subtypes, and treatment outcomes, we performed a systematic review and meta-analysis. Methods The PubMed, Embase, and Cochrane databases were searched for clinical studies related to PA and bone metabolism markers. Articles that met the criteria were screened and included in the systematic review; the data were extracted after evaluating their quality. R software (ver. 2022-02-16, Intel Mac OS X 11.6.4) was used for the meta-analysis. Results A total of 28 articles were subjected to systematic review, of which 18 were included in the meta-analysis. We found that PA patients evidenced a lower serum calcium level (mean difference [MD] = –0.06 mmol/L, 95% confidence interval [CI]: −0.10 ~ −0.01), a higher urine calcium level (MD = 1.29 mmol/24 h, 95% CI: 0.81 ~ 1.78), and a higher serum parathyroid hormone (PTH) level (MD = 2.16 pmol/L, 95% CI: 1.57 ~ 2.75) than did essential hypertension (EH) subjects. After medical treatment or adrenal surgery, PA patients exhibited a markedly increased serum calcium level (MD = –0.08 mmol/L, 95% CI: –0.11 ~ –0.05), a decreased urine calcium level (MD = 1.72 mmol/24 h, 95% CI: 1.00 ~ 2.44), a decreased serum PTH level (MD = 2.67 pmol/L, 95% CI: 1.73 ~ 3.62), and an increased serum 25-hydroxyvitamin D (25-OHD) level (MD = –6.32 nmol/L, 95% CI: –11.94 ~ –0.70). The meta-analysis showed that the ser um PTH level of unilateral PA patients was significantly higher than that of bilateral PA patients (MD = 0.93 pmol/L, 95% CI: 0.36 ~ 1.49) and the serum 25-OHD lower than that of bilateral PA patients (MD = –4.68 nmol/L, 95% CI: –7.58 ~ 1.77). There were, however, no significant differences between PA and EH patients of 25-OHD, or BMD of femoral neck and lumbar spine. BMDs of the femoral neck or lumbar spine did not change significantly after treatment. The meta-analytical results were confirmed via sensitivity and subgroup analyses. Conclusion Excess aldosterone was associated with decreased serum calcium, elevated urinary calcium, and elevated PTH levels; these effects may be enhanced by low serum 25-OHD levels. The risks of OP and fracture might be elevated in PA patients, especially unilateral PA patients, but could be reduced after medical treatment or adrenal surgery. In view, however, of the lack of BMD changes, such hypothesis needs to be tested in further studies.